Produção, caracterização e aplicação de fotocatalisadores heterogêneos a partir de pilhas alcalinas pós consumo - Viana, Guenther Carlos Couto (2022)
The complex negative impacts generated by contaminants of emerging concern to the environment have become a challenge to water and effluent treatment, and with that new efficient strategies need to be studied, such as heterogeneous photocatalysis. In the quest to make this process economically and environmentally viable, the use of solar radiation and the insertion of waste, such as post-consumer alkaline batteries, to replace the inputs used in the production of catalysts have been studied. The present work aimed to investigate the use of electrolytic paste from post-consumer batteries directly as catalysts, as well as to characterize and apply them in solar photocatalytic processes. The electrolytic pastes of two different batteries, Panassonic Super Hyper (SH) and Panassonic Alkaline (AK), which were calcined at 500°C and characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Diffuse Reflectance Spectroscopy in the of UV-Visible (DRS). It started with the use of a mixed catalyst of titanium dioxide (TiO2) and the electrolytic paste of the SH batteries, and due to the unsatisfactory results in this test, it was sought to determine the optimal conditions for the direct application of the electrolytic pastes of the SH and AK batteries in the degradation of methylene blue - considered as a model compound - through the association of different Design of Experiments (DoE) methodologies. The optimal condition obtained for SH was a catalyst concentration of 1.6g/L and a pH of 11.2, reaching 72.2% removal, while for AK it was obtained 1.5g/L of catalyst and pH 11.2, reaching an efficiency of 96.6%, it is noteworthy that both materials showed good photocatalytic activity until the third recycle. In order to verify if the treatment added toxicity, a phytotoxicity test was carried out on Lactuca Sativa (lettuce) seeds, where no increase in germination inhibition was observed. Due to its superiority, the catalyst obtained from the AK cell was used in the degradation of the drug, Diazepam. It was investigated at the optimal pH of the previous step (11.2) and at the natural pH of the solution (6.8), with a removal, after 2 hours, of 70.7% and 79.7%, respectively. In view of the above, it can be concluded that the direct application of electrolytic pastes from the cells studied in heterogeneous solar photocatalysis processes were efficient in the treatment of contaminants of emerging concern.